Book Review. Serge Goriely / Jean-Luc Maroy / Arnaud Join-Lambert (eds.), Visions et apparitions au cinéma: L’instant de la révélation - Yazbek, Elie (Journal for religion, film and media, 2024)
Review of the anthology Visions et apparitions au cinéma. L'instant de la révélation (2023) by Serge Goriely, Jean-Luc Maroy, and Arnaud Join-Lambert.